Against Mixed Epistemology - Joe Milburn (Principia: An International Journal of Epistemology)
We can call any reductive account of knowledge that appeals to both safety and ability conditions a mixed account of knowledge. Examples of mixed accounts of knowledge include Pritchard’s (2012) Anti-Luck Virtue Epistemology, Kelp’s (2013) Safe-Apt account of knowledge, and Turri’s (2011) Ample belief account of knowledge. Mixed accounts of knowledge are motivated by well-known counterexamples to pure safety and pure ability accounts of knowledge. It is thought that by combining both safety and ability conditions we can give an extensionally adequate reductive account of knowledge. In this paper I argue that the putative counterexamples to pure safety and pure ability accounts of knowledge fail to motivate mixed accounts of knowledge. In particular, I argue that if the putative counterexamples are problematic for safety accounts they are problematic for ability accounts and vice-versa. The reason for this, I argue, is that the safety condition and ability condition should be understood as alternative expressions of the same intuition — that knowledge must come from a reliable source.